Risk Assessment for Human-Robot Collaboration in an automated warehouse scenario - Inam, Rafia; Raizer, Klaus; Hata, Alberto; Souza, Ricardo; Forsman, Elena; Cao, Enyu; Wang, Shaolei (Proceedings (IEEE International Conference on Emerging Technologies and Factory Automation), 2018)
Collaborative robotics is recently taking an ever-increasing role in modern industrial environments like manufacturing, warehouses, mining, agriculture and others. This trend introduces a number of advantages, such as increased productivity and efficiency, but also new issues, such as new risks and hazards due to the elimination of barriers between humans and robots. In this paper we present risk assessment for an automated warehouse use case in which mobile robots and humans collaborate in a shared workspace to deliver products from the shelves to the conveyor belts. We provide definitions of specific human roles and perform risk assessment of human-robot collaboration in these scenarios and identify a list of hazards using Hazard Operability (HAZOP). Further, we present safety recommendations that will be used in risk reduction phase. We develop a simulated warehouse environment using V-REP simulator. The robots use cameras for perception and dynamically generate scene graphs for semantic representations of their surroundings. We present our initial results on the generated scene graphs. This representation will be employed in the risk assessment process to enable the use of contextual information of the robot's perceived environment, which will be further used during risk evaluation and mitigation phases and then on robots' actuation when needed.